Pengembangan Bumdes Sidowayah Kecamatan Polanharjo Kabupaten Klaten Jawa Tengah - Allwar Allwar; Tuasikal Muhammad Amin; Soni Laksono (UII, 2018)
Sidowayah Village is a growth area that is also a region that is designed as a growth area of Polanharjo Sub-district of Klaten Regency. Sidowayah Village is a strategic area with abundant water resource potential that can be managed as BUMDes potential and become a pilot at the sub-district level. With the introduction of UK KKN students is to encourage a more optimal change in the direction of development in the management of institutional, management and human resources. The problem faced by the village is not fully designed the management of water resources utilization Umbul Kemanten in order to be a supporter of village economic development as a whole. In this case the role of students is to assist the village to provide assistance in the changes and structuring of business institutions that lead to the BUMDes that are converted as the basis of creative economy for driving and supporting productive economic growth. Some of the main activities that students will undertake to help solve problems are to help design the rules and administration of the village business, help accompany the business plan of the village business units, design the village tourism profile maps (in the context of village tourism) and culinary tours, which will integrate with village businesses, encourage and design the distribution of Web-based village-scale business units.